Effect of Campaign Costs, Cost of Production Development and Distribution Channels Cost Of Sales - Triswanto, Heri; ., Triyanto (JURNAL STIE SEMARANG, 2016)
In general, institutions or organizations that seek profit (profit oriented) developed a performance management system on the basis of financial measures. It is of course different for-profit institutions. This study examines the performance of employees in government institutions (non-profit) by taking into account non-financial variables: education, motivation and ability. The purpose of this study was to examine the influence of Education, Work Motivation and Job Skills on employee performance. This research is a survey by taking samples of all employees of Kantor Dinas Pendapatan Pengelolaan Keuangan dan Asset Daerah Kabupaten Grobogan totaling 93 employees. The research instrument first tested for validity and reliability. The analysis tool used is multiple linear regression test series beginning with the classical assumption test to ensure that the regression model to estimate an unbiased and trustworthy testing, Best Linear Unbiased Estimator (BLUE). To test the hypothesis used t test and F, as well as the test of determination (R ²). The results show that in partial Educational positive and significant impact on employee performance and work motivation but not significant positive effect on employee performance. Only variables Job Skills is a significant negative effect on employee performance. But simultaneously variables of Education, Employment and Job Skills Motvasi significant effect on employee performance, with Adjusted R Square of 0.628 which means about 62.8% variation of employee performance can be explained by the variable Education, Work Motivation and Job Skills.